Cryptographic adaptation of the middle square generator - Hana Ali-Pacha; Naima Hadj-Said; Adda Ali-Pacha; Mohamad Afendee Mohamed; Mustafa Mamat (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Currently, cryptography plays a major role in various computer and technological applications. With the high number of internet users, the use of cryptography to provide information security has become a priority. Several applications such as e-mails, electronic banking, medical databases and e-commerce require the exchange of private information. While, if the connection is not secure, this sensitive information can be attacked. The best-known cryptographic systems rely on the generation of random numbers, which are fundamental in various cryptographic applications such as key generation and data encryption. In what follows, we want to use pseudo-random sequences generated by the middle square generator. In this work, it must be possible to estimate that the data produced has random characteristics, knowing that the algorithm used is deterministic. Overall, this paper focuses on the testing of pseudo-random sequences generated by the middle square generator and its use in data encryption.